Type I Interferons, Autophagy and Host Metabolism in Leprosy - Toledo Pinto, Thiago Gomes; Batista-Silva, Leonardo Ribeiro; Medeiros, Rychelle Clayde Affonso; Lara, Flávio Alves; Moraes, Milton Ozório (Frontiers in Immunology, 2018)
For those with leprosy, the extent of host infection by Mycobacterium leprae and the progression of the disease depend on the ability of mycobacteria to shape a safe environment for its replication during early interaction with host cells. Thus, variations in key genes such as those in pattern recognition receptors (NOD2 and TLR1), autophagic flux (PARK2, LRRK2, and RIPK2), effector immune cytokines (TNF and IL12), and environmental factors, such as nutrition, have been described as critical determinants for infection and disease progression. While parkin-mediated autophagy is observed as being essential for mycobacterial clearance, leprosy patients present a prominent activation of the type I IFN pathway and its downstream genes, including OASL, CCL2, and IL10. Activation of this host response is related to a permissive phenotype through the suppression of IFN-γ response and negative regulation of autophagy. Finally, modulation of host metabolism was observed during mycobacterial infection. Both changes in lipid and glucose homeostasis contribute to the persistence of mycobacteria in the host. M. leprae-infected cells have an increased glucose uptake, nicotinamide adenine dinucleotide phosphate generation by pentose phosphate pathways, and downregulation of mitochondrial activity. In this review, we discussed new pathways involved in the early mycobacteria–host interaction that regulate innate immune pathways or metabolism and could be new targets to host therapy strategies.